Bite seg i tungen og suge det en kan: Om frie teatergrupper i Berlin - Ingebjørg Fjell, Tove (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
(Off-)theatre actors and audiences often interpret performances differently, often due to different understandings of artistic communication. In the article the author seeks to explore the field of tension between, on the one hand, the search for individual and unique experiences, and, on the other hand, the natural, the authentic, and the intrinsically conformable. Methodologically, the study is based on observational participation in Berlin.